The Influence of Epigenetic Modifications on Metabolic Changes in White Adipose Tissue and Liver and Their Potential Impact in Exercise - Axsom, Jessie E.; Schmidt, Heath D.; Matura, Lea Ann; Libonati, Joseph R. (Frontiers in Physiology, 2021)
Background: Epigenetic marks are responsive to a wide variety of environmental stimuli and serve as important mediators for gene transcription. A number of chromatin modifying enzymes orchestrate epigenetic responses to environmental stimuli, with a growing body of research examining how changes in metabolic substrates or co-factors alter epigenetic modifications. Scope of Review: Here, we provide a systematic review of existing evidence of metabolism-related epigenetic changes in white adipose tissue and the liver and generate secondary hypotheses on how exercise may impact metabolism-related epigenetic marks in these tissues. Major Conclusions: Epigenetic changes contribute to the complex transcriptional responses associated with white adipose tissue lipolysis, hepatic de novo lipogenesis, and hepatic gluconeogenesis. While these metabolic responses may hypothetically be altered with acute and chronic exercise, direct testing is needed.